State and nobility in early modern Germany : the knightly feud in Franconia, 1440-1567 - Zmora, Hillay, 1964- (Cambridge studies in early modern history., 1997)
One of the most striking features of late medieval and early modern German was the countless feuds carried out by nobles. A constant threat to law and order, these feuds have commonly been regarded as a manifestation of the decline - economic and otherwise - of the nobility. This study shows that the nobility was not in crisis at this time. Nor were feuds merely banditry by another name. Rather, they were the result of an interplay between two fundamental processes: princely state-building, and social stratification among the nobility. Offering a new paradigm for understanding the German nobility, this book argues that the development of the state made proximity to princes the single most decisive factor in determining the fortune of a family. The result was a violent competition among the nobility over resources which were crucial to the princes. Feuds played a central role in this struggle that eventually led to the formation of an elite of noble families on whose power and wealth the princely state depended.